2017
DOI: 10.1111/pce.12969
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of barley roots in high‐pH nutrient solution is supported by both cell proliferation and differentiation in the root apex

Abstract: Many crops grow well on neutral or weakly acidic soils. The ability of roots to elongate under high-external pH would be advantageous for the survival of plants on alkaline soil. We found that root elongation was promoted in some plant species in alkaline-nutrient solution. Barley, but not tomato, root growth was maintained in pH 8 nutrient solution. Fe and Mn were absorbed well from the pH 8 nutrient solution by both barley and tomato plants, suggesting that the different growth responses of these two species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Therefore, barley grown in these areas is at high risk of low Fe availability. As we have reported [42], even a small change in pH significantly impacted the elongation of barley roots, indicating that such a slight increase of soil pH could alter the energy metabolism. In the case of Ambrosia artemisiifolia, pH 7 is a serious environment, inhibiting the formation of flowers and pollen and delaying their growth [43].…”
Section: New Insights On Barley Cultivation In Respect Of Fe Nutritionsupporting
confidence: 56%
“…Therefore, barley grown in these areas is at high risk of low Fe availability. As we have reported [42], even a small change in pH significantly impacted the elongation of barley roots, indicating that such a slight increase of soil pH could alter the energy metabolism. In the case of Ambrosia artemisiifolia, pH 7 is a serious environment, inhibiting the formation of flowers and pollen and delaying their growth [43].…”
Section: New Insights On Barley Cultivation In Respect Of Fe Nutritionsupporting
confidence: 56%
“…Several studies have shown that plants perceive and respond in different ways to high pH, high HCO 3 − , or iron deficiency [9], and the mechanisms of carbonate tolerance remain largely unknown. Alkaline pH per se can affect root growth by inhibiting cell division and elongation [10]; ethylene modulates this effect increasing the expression of AUX1 and of genes responsible for auxin synthesis [11]. Crosstalk between jasmonate and ethylene in response to alkalinity stress has been reported [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…One way for plants to adapt to high pH is to accumulate small metabolites with buffering function, especially organic acids, for adjusting the internal pH value. However, the adjusting of external and internal pH is a process that consumes energy and reduces plant growth simultaneously [10].…”
Section: Introductionmentioning
confidence: 99%
“…The Yellow River Delta (YRD) area has been affected by severe soil salinization issues, with high groundwater salinity (5-30 g L −1 ), shallow groundwater levels (1-2 m below the soil surface), and low organic carbon content (averaged 6.09 g kg −1 ) [5][6][7][8]. In this region, high soil pH and an excess of sodium (Na) ions result in poor soil structure and low water infiltration, inhibiting crop growth and nutrient absorption and, ultimately, reducing crop yields [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%